UJI VALIDITAS DAN UJI RELIABILITAS PADA PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) DI PT. BARKAH BORNEO MEMBANGUN - Syantika Rini, Tati Febrianti; Purwandari, Diana; Fernanda Badrusalam, Rio Rizky (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
Corporate social responsibility (CSR) is a form of corporate social responsibility to the community around the company. The CSR program implemented by PT. Barkah Borneo Membangun (BBM) is an economic program and a social program. This study aims to conduct a Validity Test and Reliability Test on the CSR program and community response to the CSR Program. This study uses a quantitative approach by distributing questionnaires. The CSR program at PT. BBM has 4 indicators of question items, namely about the quality of public facilities and infrastructure, increasing community independence economically, the level of quality of social relations between the company and the community, and the level of community satisfaction. The sample studied was 100 respondents, consisting of 20 stone miners, 20 employees of the local community PT, 30 people from the community study program, and 30 people from the social program for the community. The Validity Test uses the product moment correlation formula to calculate the correlation coefficient (r) while the Reliability Test uses the Cronbach Alpha formula with a significance level of 5%. If the reliability figure (α) is more than 0.7 (reference value) then the measuring instrument is said to be reliable. All instruments in the CSR program at PT. BBM is concluded to be valid, this can be proven by all r_count values ​​> r_table for each variable. It can also be concluded as Reliable because all instruments in the CSR program at PT. BBM have α_count values ​​> 0.7 for each variable.